2015
DOI: 10.1016/j.cya.2015.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of corporate risk disclosure in large Spanish companies: a snapshot

Abstract: Improvements in risk disclosure have been an important part of the corporate governance reforms. This paper is intended to identify the factors that explain the extent to which a sample of 35 listed Spanish firms disclose risk-related information. This study focuses on the risk disclosures made in the corporate governance reports during the year 2009. Using the content analysis technique an index was developed in order to assess the amount and quality of the risk information disclosed by Spanish companies. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 48 publications
8
20
0
2
Order By: Relevance
“…Given the scarce research in interim reports, it must be taken into account that the data obtained are mostly compared to that obtained in the research in annual reports. TRD is positively related to size (p<0.01) confirming the existing literature findings (Elshandidy & Neri, 2014;Hassan, 2014;Madrigal et al, 2015;Linsley & Shrives, 2006;Mohobbot, 2005;Ntim et al, 2013;Oliveira et al, 2011;Semper & Beltrán, 2009). Profitability (ROE) did not show association with risk disclosure indexes in line with Al-Shammari (2014), Elshandidy, Fraser, and Hussainey (2013) and Elzahar and Hussainey (2012).…”
Section: Determinants Of Corporate Risk Disclosure -Audit Qualitysupporting
confidence: 82%
See 2 more Smart Citations
“…Given the scarce research in interim reports, it must be taken into account that the data obtained are mostly compared to that obtained in the research in annual reports. TRD is positively related to size (p<0.01) confirming the existing literature findings (Elshandidy & Neri, 2014;Hassan, 2014;Madrigal et al, 2015;Linsley & Shrives, 2006;Mohobbot, 2005;Ntim et al, 2013;Oliveira et al, 2011;Semper & Beltrán, 2009). Profitability (ROE) did not show association with risk disclosure indexes in line with Al-Shammari (2014), Elshandidy, Fraser, and Hussainey (2013) and Elzahar and Hussainey (2012).…”
Section: Determinants Of Corporate Risk Disclosure -Audit Qualitysupporting
confidence: 82%
“…In the last decades there was an increase of research about corporate risk disclosure (Abraham & Cox, 2007;Allini, Manes, Francesca, & Hussainey, 2016;Madrigal, Guzmán, & Guzmán, 2015;Linsley & Shrives, 2006;Oliveira, Rodrigues, & Craig, 2011); most of them conclude that risk information is not enough (Kravet & Muslu, 2013), triggering doubts about the quality and utility of disclosed risk information (Abraham & Shrives, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Las empresas cotizadas en el mercado continuo español que estuviesen incluidas en el índice bursátil del IBEX 35 durante el período 2004-2008 constituyen la población de partida, al ser éstas más susceptibles de una mayor transparencia informativa (Hernández, Aibar, & Aibar, 2015). El IBEX 35 es el principal índice bursátil de referencia de la bolsa española.…”
Section: Definición De La Población Y Elección De La Muestraunclassified
“…In weakly governed Italian firms, mandatory disclosure levels were observed to have significant positive association with firm size. Madrigal et al 85 , observed significant positive association of level of risk disclosure in Spanish companies with firm size, firm risk level and nature of industry. AlHadi et al 86 , observed significant and positive association of level of market risk disclosures with existence of dedicated risk committees in companies listed in the GCC (Gulf co-operation council) countries and the presence of directors representing the government on the board.…”
Section: Association Of Corporate Risk Disclosures With Firm Govementioning
confidence: 99%